2007
DOI: 10.1038/sj.emboj.7601687
|View full text |Cite
|
Sign up to set email alerts
|

Anthrax lethal toxin paralyzes actin-based motility by blocking Hsp27 phosphorylation

Abstract: Inhalation of anthrax causes fatal bacteremia, indicating a meager host immune response. We previously showed that anthrax lethal toxin (LT) paralyzes neutrophils, a major component of innate immunity. Here, we have found that LT also inhibits actin-based motility of the intracellular pathogen Listeria monocytogenes. LT inhibition of actin assembly is mediated by blockade of Hsp27 phosphorylation, and can be reproduced by treating cells with the p38 mitogen-activated protein (MAP) kinase inhibitor SB203580. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
114
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(117 citation statements)
references
References 38 publications
3
114
0
Order By: Relevance
“…S6). These results are consistent with previous findings that HSP27 is a direct inhibitor of actin polymerization (20,21).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…S6). These results are consistent with previous findings that HSP27 is a direct inhibitor of actin polymerization (20,21).…”
Section: Discussionsupporting
confidence: 83%
“…It is well established that HSP27 directly inhibits actin polymerization by capping the barbed end of actin (20), where rapid addition of actin monomers occurs. Additionally, HSP27 can sequester G-actin monomers (21). As a consequence of either action, G-actin cannot bind to the plus end of F-actin and be further aggregated by myosin to form contractile stress fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S5), whereas one of HSP27's natural kinases in humans, MAPKAP2, can phosphorylate only three sites (Ser-15, Ser-78, and Ser-82) (56). This system differs from that used by Listeria monocytogenes, which manipulates the host p38 MAPK pathway to indirectly cause the phosphorylation of HSP27 to affect actin remodeling (54). More recently, two groups showed that SteC targets Cdc24 in yeast (57) and MEK in mammalian cells (9).…”
Section: Fig 2 Host Cell-specific Modulation Of Cellular Processes mentioning
confidence: 99%
“…How this might occur at the atomic level is still an open question in the HSP27 field, although it seems likely that phosphorylation of HSP27 induces its disassociation from actin monomers, resulting in promotion of F-actin assembly from the newly freed actin monomers (54,55). One prediction of this would then be that multiply phosphorylated forms of HSP27 could further accelerate actin polymerization.…”
Section: Fig 2 Host Cell-specific Modulation Of Cellular Processes mentioning
confidence: 99%